1995
DOI: 10.1093/humrep/10.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Identification of nitric oxide synthase in human uterus

Abstract: The aim of this study was to investigate the presence of nitric oxide synthase (NOS) in human uterus. Tissues were obtained at operation from 10 women undergoing hysterectomy for benign disease. In-situ hybridization was used to determine the distribution of mRNA for NOS with a 483 bp digoxigenin-labelled antisense riboprobe. Localization of NOS was detected by (i) immunocytochemistry using a monoclonal antibody raised against bovine constitutive endothelial NOS, and (ii) NADPH diaphorase, which has been sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
82
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(89 citation statements)
references
References 0 publications
6
82
0
1
Order By: Relevance
“…The importance of NO as a regulator of early developmental events has been established by studies that demonstrated that the oocyte and preimplantation embryo are exposed to NO, and oocyte maturation, preimplantation embryogenesis and implantation require NO (Biswas et al, 1998;Gagioti et al, 2000;Maul et al, 2003;Novaro et al, 1997;Purcell et al, 1999;Sengoku et al, 2001;Shukovski and Tsafriri, 1995;Telfer et al, 1995). Moreover, in vitro and in vivo studies showed that administration of either NOS inhibitors or NO donors hinders development of preimplantation embryos (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of NO as a regulator of early developmental events has been established by studies that demonstrated that the oocyte and preimplantation embryo are exposed to NO, and oocyte maturation, preimplantation embryogenesis and implantation require NO (Biswas et al, 1998;Gagioti et al, 2000;Maul et al, 2003;Novaro et al, 1997;Purcell et al, 1999;Sengoku et al, 2001;Shukovski and Tsafriri, 1995;Telfer et al, 1995). Moreover, in vitro and in vivo studies showed that administration of either NOS inhibitors or NO donors hinders development of preimplantation embryos (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…NOS activity has been reported to be present in the endometrium of nonpregnant sheep (24). Recently, Telfer et al (25) demonstrated the presence of eNOS mRNA and protein in human endometrium and myometrium using in situ hybridization and immunocytochemistry. Recent work has shown that human endometrial glandular cells express eNOS mRNA throughout the menstrual cycle, while the expression of iNOS mRNA is confined to epithelial glands isolated from menstrual endometrium (26).…”
Section: Discussionmentioning
confidence: 99%
“…In mammals it is a potent vasodilator with short half-life, and an important cell signaling molecule that is involved in many physiological and pathological processes (Hou, 1999). It has been reported that localized NO synthesis in reproductive tissue plays an important role in regulating certain reproductive functions such as endometrial, cervical and myometrial activity (Telfer, 1995), embryo implantation (Battaglia, 2003) as well as embryo development (Chwalisz, 1999). While it is apparent from these studies that NO plays key roles in early pregnancy and even parturition, its concentration must be tightly regulated as it has also been reported that aberrant NO levels have been associated with embryo cytotoxicity (Barroso, 1999), early embryo loss (Haddad, 1995), as well as preterm labor (Cella, 2010).…”
Section: Introductionmentioning
confidence: 99%